2022
DOI: 10.36103/ijas.v53i6.1640
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Egg Shell and Spots Colour on the Quality of Hatching Eggs Derived From Three Lines of Local Quail

Abstract: This study was carried out to analyze the impact of lines, egg shell colour and intraction between (Line ⁎ eggshell colours) on egg quality characteristics and hatching parameters assess the correlation between these traits in three local quail eggs (desert, brown and white). A total of 409 eggs were collected from female quails during 16 weeks divided into five groups on the basis of eggshell colour and spot colour for each line. The results revealed  that there were significant (P≤0.05) variances among lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…None of the results, however, were comparable to the previous ones, which showed that the eggshell color of pheasant eggs, whether blue, light brown, dark brown, or olive green, had no discernible effect on the egg's weight or the eggshell ( Godfrey, 1947 ; Ahmed, 2022 ). While our findings were perfectly consistent with a previous study that reported significant differences in egg sizes, width, and form, the egg shape index was not significant ( Choprakarn et al, 1998 ).…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…None of the results, however, were comparable to the previous ones, which showed that the eggshell color of pheasant eggs, whether blue, light brown, dark brown, or olive green, had no discernible effect on the egg's weight or the eggshell ( Godfrey, 1947 ; Ahmed, 2022 ). While our findings were perfectly consistent with a previous study that reported significant differences in egg sizes, width, and form, the egg shape index was not significant ( Choprakarn et al, 1998 ).…”
Section: Discussioncontrasting
confidence: 76%
“…It was found that the hatchability qualities of Japanese quail eggs were affected by the color of their eggshells ( Gutiérrez et al, 2021 ). Furthermore, it was revealed that in local quail, breed differences and eggshell color had a significant influence on egg quality measures and hatchability indications ( Ahmed, 2022 ). We found that the hatching rate of chicks from eggs with very bright shells was much lower than that of eggs with darkish shells, which was consistent with previous research on chickens ( Godfrey, 1947 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The egg quality (exterior and inner metrics) including egg width, egg length, shell weight, shell thickness, albumen %, yolk%, yolk index, Haugh unit, and unit surface shell weight, were determined as recommended by Romanoff and Romanoff (1949) . The external egg quality characteristics such as egg shape index, shell ratio, were determined as previously described by Ahmed (2022) . The albumen and yolk were separated from one another without causing any damage to the egg yolk, and the third process involved determining the weight of the egg yolk.…”
Section: Methodsmentioning
confidence: 99%